Transcriptional elongation of non-coding bxd RNAs promoted by the Trithorax TAC1 complex represses Ubx by a transcriptional interference mechanism - Petruk, Svetlana (2006)
Much of the genome is transcribed into long non-coding RNAs (ncRNAs). Previous data suggested that bithoraxoid (bxd) ncRNAs of the Drosophila bithorax complex prevent silencing of Ultrabithorax (Ubx), and recruit activating proteins of the trithorax group to their maintenance elements. We found that, surprisingly, Ubx and several bxd ncRNAs are expressed in non-overlapping patterns in both embryos and imaginal discs, suggesting that transcription of these ncRNAs is associated with repression, not activation, of Ubx. Our data rule out siRNA or miRNA-based mechanisms for repression by bxd ncRNAs. Rather, ncRNA transcription itself, acting in cis, represses Ubx. The Trithorax complex TAC1 binds the Ubx coding region in nuclei expressing Ubx, and the bxd region in nuclei not expressing Ubx. We propose that TAC1 promotes the mosaic pattern of Ubx expression by facilitating transcriptional elongation of bxd ncRNAs, which represses Ubx transcription.